The students on the right hand side had better overall results
There were less people on the left hand side of the room this affects the average even with the right hand side having two zeros, another thing which the left hand side didn’t have.
Hope I helped
The equation of the line is ![5x+y-38=0](https://tex.z-dn.net/?f=5x%2By-38%3D0)
Step-by-step explanation:
The slope is ![m=-5](https://tex.z-dn.net/?f=m%3D-5)
Also, the line passes through the points ![(7,3)](https://tex.z-dn.net/?f=%287%2C3%29)
To find a line with slope
that passes through the points
, let us use the equation of a line with slope that passes through the point is given by
where m is the slope and
are the points
.
Thus, substituting the values in the equation of a line, we get,
![(y-3)=-5(x-7)](https://tex.z-dn.net/?f=%28y-3%29%3D-5%28x-7%29)
Multiplying the term
by -5, we get,
![y-3=-5 x+35](https://tex.z-dn.net/?f=y-3%3D-5%20x%2B35)
Adding both sides by 5x,
![5x+y-3=35](https://tex.z-dn.net/?f=5x%2By-3%3D35)
Subtracting 35 from both sides of the equation,
![5x+y-38=0](https://tex.z-dn.net/?f=5x%2By-38%3D0)
Thus, the equation of the line is ![5x+y-38=0](https://tex.z-dn.net/?f=5x%2By-38%3D0)
Answer:
d is answer have a great day
Answer:
![m\angle B=m\angle C=120^{\circ}](https://tex.z-dn.net/?f=m%5Cangle%20B%3Dm%5Cangle%20C%3D120%5E%7B%5Ccirc%7D)
![m\angle A=m\angle D=60^{\circ}](https://tex.z-dn.net/?f=m%5Cangle%20A%3Dm%5Cangle%20D%3D60%5E%7B%5Ccirc%7D)
Step-by-step explanation:
Trapezoid ABCD is isosceles trapezoid, because AB = CD (given). In isosceles trapezoid, angles adjacent to the bases are congruent, then
Since BK ⊥ AD, the triangle ABK is right triangle. In this triangle, AB = 8, AK = 4. Note that the hypotenuse AB is twice the leg AK:
If in the right triangle the hypotenuse is twice the leg, then the angle opposite to this leg is 30°, so,
![m\angle ABK=30^{\circ}](https://tex.z-dn.net/?f=m%5Cangle%20ABK%3D30%5E%7B%5Ccirc%7D)
Since BK ⊥ AD, then BK ⊥ BC and
![m\angle KBC=90^{\circ}](https://tex.z-dn.net/?f=m%5Cangle%20KBC%3D90%5E%7B%5Ccirc%7D)
Thus,
![m\angle B=30^{\circ}+90^{\circ}=120^{\circ}\\ \\m\angle B=m\angle C=120^{\circ}](https://tex.z-dn.net/?f=m%5Cangle%20B%3D30%5E%7B%5Ccirc%7D%2B90%5E%7B%5Ccirc%7D%3D120%5E%7B%5Ccirc%7D%5C%5C%20%5C%5Cm%5Cangle%20B%3Dm%5Cangle%20C%3D120%5E%7B%5Ccirc%7D)
Now,
![m\angle A=m\angle D=180^{\circ}-120^{\circ}=60^{\circ}](https://tex.z-dn.net/?f=m%5Cangle%20A%3Dm%5Cangle%20D%3D180%5E%7B%5Ccirc%7D-120%5E%7B%5Ccirc%7D%3D60%5E%7B%5Ccirc%7D)